A multicenter cohort study of severe dengue and critically ill influenza patients with elevated cardiac troponin-I: Difference clinical features and high mortality. Issue 47 (May 2022) - Lee, Ing-Kit; Chen, Yen-Hsu; Huang, Chung-Hao; Hsu, Jui-Chi; Chang, Yi-Chin; Kuo, Hong-Jie; Tai, Chien-Hsiang; Lee, Nan-Yao
Abstract: Background: As cardiac involvement can cause serious complications and death, understanding its role in acute dengue and influenza virus infections is important. Methods: We provide a comparative evaluation of severe dengue and critically ill influenza patients with elevated cardiac troponin-I (cTnI) from 2014 to 2019. Inclusion criteria included patients in which cTnI test were ordered. Patient without cTnI test was excluded. Results: During the study period, 82 (41 severe dengue and 41 critically ill influenza) patients had cTnI elevations, and 81 (35 severe dengue and 46 critically ill influenza) patients had a single normal cTnI test. Severe dengue patients with cTnI elevations had a significantly higher incidences of acute kidney injury, gastrointestinal bleeding, early mortality (≤7 after illness onset) and in-hospital mortality than those with severe dengue and single normal cTnI test. Significantly higher aspartate aminotransferase (AST) levels and higher incidence of gastrointestinal bleeding was observed in critically ill influenza patients with cTnI elevations compared to critically ill influenza patients with single normal cTnI measurement. Of the patients with cTnI elevations, the early and in-hospital mortality rates were 53.6% and 65.8%, respectively, in severe dengue patients, and 7.3% and 46.3%, respectively, in critically ill influenza patients. Significantly higher early mortality rates were observed in severe dengue patients with elevated cTnI levels than in critically ill influenza patients with cTnI elevations. Critically ill influenza patients with elevated cTnI levels had significantly higher incidences of pneumonia, pneumothorax, and bacteremia than severe dengue patients with cTnI elevations. Multivariate analysis revealed elevated AST (>1000U/L) (95% confidence interval [CI]: 1.690–143.174) was an independent risk factor for in-hospital mortality in severe dengue patients with elevated cTnI levels. Leukocytosis (95% CI: 1.079–1.124) and thrombocytopenia (95% CI: 2.739–5.821) were independently correlated with in-hospital mortality in critically ill influenza patients with cTnI elevations. Conclusions: Differences in clinical features between severe dengue and critically ill influenza patients with cTnI elevations. High early mortality rate was observed in severe dengue patients with cardiac involvement. In contrast, most critically ill influenza patients died ≥2 weeks after the onset of illness, regardless of cTnI elevations. Our report has important clinical implications for the timely recognition and management of cardiac complication in patients with acute dengue and influenza virus infections.